Salmonella and Enterohemorrhagic Escherichia coli Serogroups O45, O121, O145 in Wheat Flour: Effects of Long-Term Storage and Thermal Treatments - Forghani, Fereidoun; den Bakker, Meghan; Liao, Jye-Yin; Payton, Alison S.; Futral, Alexandra N.; Diez-Gonzalez, Francisco (Frontiers in Microbiology, 2019)
Salmonella and enterohemorrhagic Escherichia coli (EHEC) are of serious concern in wheat flour and its related products but little is known on their survival and thermal death kinetics. This study was undertaken to determine their long-term viability and thermal inactivation kinetics in flour. Inoculation was performed using mixtures of EHEC serogroups O45, O121, O145 and Salmonella followed by storage at room temperature (23 ºC) or 35 ºC (for Salmonella). Plate counting on tryptic soy agar (TSA) and enrichment were used to assess long-term survival. For thermal studies, wheat flour samples were heated at 55, 60, 65 and 70 ºC and cell counts of EHEC and Salmonella were determined by plating. The δ-values were calculated using the Weibull model. At room temperature, EHEC serovars and Salmonella were quantifiable for 84 and 112 days, and were detectable for the duration of the experiment after 168 and 365 days, respectively. The δ-values were 2.0, 5.54 and 9.3 days, for EHEC O121, O45 and O145, respectively, 9.7 days for Salmonella. However, the only significant difference among all values was the δ-value for Salmonella and serogroup O121 (p ≤ 0.05). At 35 ºC, Salmonella counts declined to unquantifiable levels after a week and were not detected upon enrichment after 98 days. Heat treatment of inoculated wheat flour at 55, 60, 65 and 70 ºC resulted in δ-value ranges of 20.0 to 42.9, 4.9 to 10.0, 2.4 to 3.2, and 0.2 to 1.6 min, respectively, for EHEC. The δ-values for Salmonella at those temperatures were 152.2, 40.8, 17.9 and 17.4 min, respectively. The δ-values obtained for Salmonella at each temperature were significantly longer than for EHEC (p ≤ 0.05). Weibull model was a good fit to describe the thermal death kinetics of Salmonella and EHEC O45, O121 and O145 in wheat flour.